Wire rod

By adjusting the chemical composition of the wire and controlling the actual interlayer spacing distribution, the problem of wire breakage during wire drawing was solved, achieving high-efficiency wire drawing and meeting the needs of reducing costs and improving productivity.

CN121488059APending Publication Date: 2026-02-06NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480046381.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-12
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

In the existing technology, wires are prone to breakage during wire drawing, and in order to reduce manufacturing costs and improve productivity, it is desirable to omit intermediate heat treatment to improve wire drawing processability.

Method used

By adjusting the chemical composition and microstructure of the wire, particularly by controlling the average value of the true interlayer spacing and the half-width ratio of the wire in a circular cross-section, excellent wire drawing processability is ensured.

Benefits of technology

This significantly improves the wire drawing processability without requiring intermediate heat treatment, avoids wire breakage, and enhances production efficiency and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121488059A_ABST
    Figure CN121488059A_ABST
Patent Text Reader

Abstract

Provided is a wire rod having excellent drawability. In a circular cross section perpendicular to the axial direction of the wire rod, when the average value of the real interlayer spacing at a depth of 0.5 mm from the surface of the wire rod is set as LaveS (nm) and the maximum value of the real interlayer spacing is set as LmaxS (nm), LmaxS / LaveS is 1.70 or less, and in the circular cross section, the average value of the real interlayer spacing at a depth of 0.5 mm from the surface of the wire rod is set as LaveS (nm) and the maximum value of the real interlayer spacing at a depth of 0.5 mm from the surface of the wire rod is set as LmaxS (nm). FWHMc / FWHMs is 1.10-2.00, where FWHMs (nm) is the full width at half maximum of the real interlayer spacing at a depth of 0.5 mm from the surface of the wire rod, and FWHMc (nm) is the full width at half maximum of the real interlayer spacing at the center of the wire rod.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to wires, and more specifically, to wires of raw materials suitable for automotive tire cords, tire wires, bridge wires, etc. Background Technology

[0002] Steel cord, made from wire rod, can be manufactured using the following method: Prepare wire rod with a diameter of approximately 4-6 mm after hot rolling and cooling. Perform a single drawing process on the wire rod to produce a wire with a diameter of 3-4 mm. After the first drawing, perform intermediate martensitization treatment, followed by a second drawing process to produce a wire with a diameter of 1-2 mm. Perform a final martensitization treatment on this wire. Plate the final martensitized wire with brass, and then perform a final wet drawing process to produce a wire with a diameter of 0.15-0.40 mm. Further, twist multiple wires together to create twisted steel wire. Steel cord is manufactured through these processes. Additionally, tire wire, bridge wire, etc., can be manufactured by performing martensitization treatment on hot-rolled wire rod and then drawing it to produce twisted steel wire.

[0003] When wire is drawn once or multiple times, breakage is likely to occur if the drawing volume is large. To suppress such breakage, the wire (or steel wire) is usually subjected to a heat treatment called intermediate heat treatment before drawing. However, from the point of view of reducing manufacturing costs and improving productivity, it is desirable to omit intermediate heat treatment. Therefore, there is a need for further improvement in the drawability of wire.

[0004] Techniques for improving wire drawing processability have been proposed in International Publication No. 2018 / 117157 (Patent Document 1) and International Publication No. 2016 / 021556 (Patent Document 2).

[0005] The chemical composition of the wire disclosed in Patent Document 1, by mass%, contains: C: 0.90~1.20%, Si: 0.10~1.00%, Mn: 0.20~0.80%, Cr: 0.10~0.40%, Al: 0~0.002%, Ti: 0~0.002%, N: 0~0.0050%, P: 0~0.020%, S: 0~0.010%, O: 0~0.0040%, Mo: 0~0.20%, B: 0~0.0030%, with the balance consisting of Fe and impurities. The average value of %Mn+2×%Cr in the overall wire is 0.50~1.00%. The microstructure, by area fraction, is more than 90% pearlite, with the balance containing any two or more of ferrite, cementite, and bainite, and the area fraction of cementite is less than 3%. The maximum particle size of TiN is less than 15 μm. The maximum value of %Mn+2×%Cr in the region from the central axis of the wire to 1 / 10 of the wire diameter (the central part), where the S and O content is less than 1%, measured at a cross-section perpendicular to the length direction of the wire, is less than 2.0 times the average value of %Mn+2×%Cr in the entire wire. The ratio of the maximum to minimum value of %Mn+2×%Cr in the region from the outer edge of the central part to a depth of 0.1 mm on the wire surface (the peripheral part), where the S and O content is less than 1%, measured at a cross-section perpendicular to the length direction of the wire, is less than 2.0. Here, %Mn and %Cr represent the content of Mn and Cr in mass percent. In this wire, the wire drawing processability is improved by adjusting the chemical composition, the pearlite-dominated metal structure, the size of TiN, and the segregation of Mn and Cr.

[0006] The chemical composition of the wire disclosed in Patent Document 2, by mass%, contains C: 0.70~1.20%, Si: 0.10~1.2%, Mn: 0.10~1.0%, P: 0.001~0.012%, S: 0.001~0.010%, N: 0.0010~0.0050%, with the balance consisting of Fe and impurities. In this wire, in a cross-section perpendicular to the length direction, the area fraction of pearlite is 95% or more and 100% or less, the average bulk pearlite size is 10μm~30μm, and the standard deviation of the bulk pearlite size is 20μm or less. Furthermore, when C(%), Si(%) and Mn(%) are taken as the mass percentages of C, Si and Mn respectively, and Ceq. is calculated by the following formula (1), the tensile strength is 760×Ceq.+255MPa or more and 760×Ceq.+325MPa or less, and the reduction of area in the tensile test is -65×Ceq.+96(%) or more, and the standard deviation of the reduction of area is 6% or less.

[0007] Ceq.=C(%)+Si(%) / 24+Mn(%) / 6 Formula (1)

[0008] In this wire, the workability is improved by adjusting the size of the pearlite blocks.

[0009] Furthermore, unlike Patent Documents 1 and 2, Japanese Patent Application Publication No. 2012-126955 (Patent Document 3) improves wire drawing processability by adjusting the lamellar spacing of the pearlite. Specifically, the wire disclosed in Patent Document 3 contains, by mass percent, 0.68-0.86% C, 0.05-0.5% Si, and 0.1-0.8% Mn, with the balance consisting of Fe and unavoidable impurities. The microstructure of this wire has pearlite accounting for more than 95% of its area, with an average lamellar spacing L in the range of 150-300 nm. Furthermore, within the lamellar layers of this pearlite, the area with a spacing of 120 nm or less is 30% or less, and the standard deviation of the lamellar spacing is 50 nm or less. In addition, the average nodule diameter D of the pearlite is 40 μm or less, and the average nodule diameter D and the aforementioned average lamellar spacing L satisfy the relationship D < -0.1 × L + 60.

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: International Publication No. 2018 / 117157

[0013] Patent Document 2: International Publication No. 2016 / 021556

[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-126955 Summary of the Invention

[0015] The problem that the invention aims to solve

[0016] The wire drawing processability can also be improved using the techniques disclosed in Patent Documents 1 to 3. However, other techniques can also be used to improve the wire drawing processability.

[0017] The purpose of this invention is to provide wires with excellent drawing properties.

[0018] Problem Solving Methods

[0019] The chemical composition of the wire disclosed herein, by mass%, contains: C: 0.70~1.20%, Si: 0.10~1.50%, Mn: 0.10~1.00%, P: less than 0.020%, S: less than 0.020%, Al: less than 0.080%, N: 0.0010~0.0100%, O: less than 0.0050%, Cr: 0~0.50%, Co: 0~0.50%, Cu: 0~0.50%, Ni: 0~0.50%. The composition is as follows: Mo: 0~0.20%, B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, As: 0~0.050%, Sb: 0~0.050%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%, with the balance consisting of Fe and impurities. Furthermore, in a circular cross-section perpendicular to the wire's axis, when the average value of the true lamellar spacing at a depth of 0.5 mm from the wire surface is set as LaveS (nm), and the maximum value of the true lamellar spacing is set as LmaxS (nm), LmaxS / LaveS is less than 1.70. In a circular cross-section, when the half-value full width of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-value full width of the actual interlayer spacing at the center of the wire is set as FWHMc (nm), the ratio of FWHMc / FWHMs is 1.10~2.00.

[0020] The effects of the invention

[0021] The wire of this invention has excellent wire drawing processability. Attached Figure Description

[0022] Figure 1 This is a schematic diagram used to illustrate the apparent pearlite interlayer spacing and the actual pearlite interlayer spacing in microscopic tissue observation.

[0023] Figure 2 This is a schematic diagram illustrating an example of an observation plane when a section perpendicular to the axis of the wire is used as the observation plane.

[0024] Figure 3 It is Figure 2 The diagram is obtained by dividing the field of view into multiple small segments.

[0025] Figure 4 yes Figure 3 A schematic diagram of a small segment in the image.

[0026] Figure 5 Is with Figure 4Schematic diagrams of other different micro-segments.

[0027] Figure 6 Is with Figure 4 and Figure 5 Schematic diagrams of other different micro-segments. Detailed Implementation

[0028] First, the inventors investigated the chemical composition of wire materials suitable for use as raw materials in steel cord, tire wire, and bridge wire. The results showed that the chemical composition, by mass%, contained: C: 0.70-1.20%, Si: 0.10-1.50%, Mn: 0.10-1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, N: 0.0010-0.0100%, O: 0.0050% or less, Cr: 0-0.50%, Co: 0-0.50%, Cu: 0-0.50%, Ni: 0-0.50%, and Mo: 0-0.20%. When the content of B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, As: 0~0.050%, Sb: 0~0.050%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%, with the balance being Fe and impurities, it is suitable as a raw material for steel cord, tire steel wire, bridge steel wire, etc.

[0029] The inventors further investigated a method for improving the workability of wires with the aforementioned chemical composition. Here, the inventors are not concerned with the inclusions and pearlite block sizes adjusted in Patent Documents 1 and 2, but rather with the interlayer spacing of the pearlite. In Patent Document 3, the "apparent interlayer spacing" of the pearlite observed in the microstructure of a two-dimensional cross-section of the wire was determined.

[0030] Typically, microscopic tissue observation is conducted within a two-dimensional observation plane. (See reference...) Figure 1 When observing pearlite containing layered ferrite 1 and layered cementite 2 on observation plane 10, the minimum distance λ between adjacent layered cementite 2 in the pearlite within the observation plane 10, which is a two-dimensional plane, is determined. a Defined as "apparent interlayer spacing λ" a ".

[0031] On the other hand, the minimum distance λ between adjacent layered cementite 2 in pearlite in three-dimensional space is... t Defined as "true interlayer spacing λ" t ".

[0032] like Figure 1 As shown, the apparent interlayer spacing λ a The apparent interlayer spacing λ varies considerably depending on the angle Φ formed by the observation plane 10 (which is a two-dimensional plane) and the extending directions of the layered ferrite 1 and layered cementite 2. Therefore, in most cases, the apparent interlayer spacing λ a To be consistent with the actual interlayer spacing λ t Different values. In Patent Document 3, the apparent interlayer spacing λ in the observation plane is selected. a The apparent interlayer spacing was determined for a localized region with a small interlayer spacing. However, it can be considered that the effect on wire drawing processability is not limited to such localized regions; a wider range of interlayer spacings can also affect the processability. Based on the above research results, the inventors believe that the apparent interlayer spacing λ is not the only factor affecting wire drawing processability. a Instead, it refers to the true interlayer spacing λ over a wide range. t The distribution of [something] affects the wire drawing processability.

[0033] Therefore, the inventors have discovered that by using the following method, it is possible to determine the true interlayer spacing λ in wires that has not been studied to date. t The distribution of .

[0034] [Regarding the true interlayer spacing λ] t [Methods for determining the distribution]

[0035] interlayer spacing λ in wire t The distribution of [something] is determined by the following three steps.

[0036] (Step 1) Obtaining images by scanning electron microscopy (SEM)

[0037] (Step 2) Determination of apparent interlayer spacing distribution

[0038] (Step 3) Determination of the true interlayer spacing distribution

[0039] Here, the apparent interlayer spacing λ a As mentioned above, this refers to the distance between adjacent layered cementite bodies observed in a SEM image, which is a two-dimensional plane. The true interlayer spacing λ t This refers to the actual distance between layered cementite plates in three-dimensional space. Actual interlayer spacing λ t It will not appear on observation plane 10, and therefore cannot be observed in the SEM image. Therefore, in this embodiment, a mathematical approach is used, based on the apparent interlayer spacing λ. a The true interlayer spacing λ was calculated. t The following is a description of each step.

[0040] [(Step 1) Obtaining SEM images]

[0041] Cut the wire perpendicularly along its axial direction (length direction) and use its cross-section (the cross-section perpendicular to the axial direction of the wire) as the observation surface. Figure 2 This is a schematic diagram illustrating an example of an observation surface. The observation surface 10 is mirror-polished. Within 5 minutes after mirror polishing, the observation surface 10 is etched using Picral for approximately 7 seconds to reveal the microstructure. In the etched observation surface 10, SEM observations are performed at a magnification of 2000x with an accelerating voltage of 15 kV in four observation fields SA in the surface region and four observation fields CA in the central region, obtaining SEM images. Specifically, as... Figure 2 As shown, in the observation surface 10, four rectangular observation fields SA are selected at 90° intervals around the center point C1 of the observation surface 10, with a depth of 0.5 mm from the surface. Each field of view SA has a circumferential dimension of 5120 pixels and a radial dimension of 3840 pixels. The area of ​​each observation field SA is set to a rectangle with a circumferential dimension of 60 μm (5120 pixels) and a radial dimension of 45 μm (3840 pixels). Hereinafter, the four observation fields SA are referred to as the observation fields SA of the surface region.

[0042] Furthermore, taking the center C1 of the observation surface 10 as the center, four arbitrary observation fields CA are selected from a circular area with a radius of D / 8 (D is the diameter of the wire), i.e., the central area 20. Each observation field CA is set as a rectangle with a circumferential dimension of 5120 pixels and a radial dimension of 3840 pixels, and the area of ​​each observation field CA is set as a rectangle with a circumferential dimension of 60μm (5120 pixels) and a radial dimension of 45μm (3840 pixels). It should be noted that the center position of each observation field CA is set at a position D / 16 radially from the center point C1. Hereinafter, the four observation fields CA are referred to as the observation fields CA of the central area.

[0043] It should be noted that the SEM device, for example, uses the trade name JSM-7100F manufactured by Nippon Electronics Co., Ltd.

[0044] [(Step 2) Apparent interlayer spacing λ] a [Determination of the distribution]

[0045] Using the observation field of view SA of the surface region and the observation field of view CA of the central region, the apparent interlayer spacing λ obtained from the two-dimensional SEM images of the surface and central regions is calculated. a The distribution of .

[0046] like Figure 3As shown, in each SEM image (viewing field SA, viewing field CA), the SEM image is divided into tiny segments 30 of 50 pixels × 50 pixels (0.586μm × 0.586μm). It should be noted that the SEM image is 5120 pixels × 3840 pixels; therefore, dividing the SEM image into tiny segments 30 will result in regions that are not 50 pixels × 50 pixels. These regions are not considered as the apparent interlayer spacing λ. a The objects of measurement.

[0047] Figure 4 This is a schematic diagram illustrating an example of micro-segment 30. In each micro-segment, the apparent interlayer spacing λ is determined using the following method. a .like Figure 4 As shown, the line segment SG with the minimum L0 = {length of the line segment / (number of intersections between the line segment and the layered cementite 2)} is determined among the line segments that pass through the center P0 of the micro-segment and have the largest number of intersections with the layered cementite 2. Here, the length of the line segment is set as the length between the two furthest intersections P1 and P2 between the line segment and the layered cementite 2. The L0 of the determined line segment is taken as the apparent interlayer spacing λ in the micro-segment 30. a (nm). In Figure 4 In the example, the number of intersections between line segment SG and layered cementite is "4".

[0048] It should be noted that, as Figure 5 As shown, among the multiple layered cementite 2 within the micro-segment 30, the proportion NR of linear layered cementite 2 whose two ends are not connected to the edge of the micro-segment 30 exceeds 50%. More specifically, in Figure 5 In the micro-segment 30, among the seven layered cementite 2, six layered cementite 2 have ends that are not connected to the edge of the micro-segment. Therefore, the proportion NR is 86% (=6 / 7×100). Thus, if the proportion NR of layered cementite 2 with ends not connected to the edge of the micro-segment 30 exceeds 50% among the multiple layered cementite 2 within the micro-segment 30, then the micro-segment 30 is not considered as the apparent interlayer spacing λ. a The objects being measured. It should be noted that, in Figure 6 In this case, the proportion of NR is 43% (=3 / 7×100). Therefore, Figure 6 The minute segment 30 was used as the measurement object.

[0049] Using the methods described above, the apparent interlayer spacing λ in the surface region can be calculated. a Distribution and apparent interlayer spacing λ in the central region a The distribution of .

[0050] [(Step 3) Determination of the true interlayer spacing distribution]

[0051] As described above, the apparent interlayer spacing λ obtained from the SEM image, which is a two-dimensional plane, is... a The distribution of the wire and the actual interlayer spacing λ t The distributions are different. Therefore, equation (a) is used to evaluate the apparent interlayer spacing λ obtained in step 2. a The distribution is fitted to obtain the true interlayer spacing λ. t The distribution of λ. Here, equation (a) shows the apparent interlayer spacing λ. a The distribution of the actual interlayer spacing λ t The formula relating the distribution of.

[0052] [Mathematical Expression 1]

[0053]

[0054] In equation (a), λ a λ represents the apparent interlayer spacing. t ρ(λ) represents the actual interlayer spacing. a G(λ) represents the distribution of apparent interlayer spacing. t ) represents the actual interlayer spacing λ t The distribution of G(λ). t Let be the Gaussian distribution function, represented by equation (b). In equation (b), A, B, and C are the fitting parameters.

[0055] [Mathematical Expression 2]

[0056]

[0057] As mentioned above, the apparent interlayer spacing λ a Depends on Figure 1 The layer orientation angle Φ is shown in the figure. Therefore, it is necessary to determine the apparent interlayer spacing λ. a Convert to actual interlayer spacing λ t .like Figure 1 As shown, the apparent interlayer spacing λ a Compared to the actual interlayer spacing λ t It satisfies equation (1).

[0058] [Mathematical Expression 3]

[0059]

[0060] Furthermore, Φ space and λ a The spatial relationship is represented by equation (2).

[0061] ρ(Φ)dΦ=ρ(λ a )dλ a (2)

[0062] In the formula, ρ(Φ) and ρ(λ) a) is the probability density function. Apparent interlayer spacing λ a It is irregular (random) relative to the observation surface 10, therefore, ρ(λ) a ) is represented by equation (3).

[0063] ρ(λ a ) = const. (3)

[0064] Based on equations (1) to (3), in the actual interlayer spacing λ t In the absence of distribution, the apparent interlayer spacing λ a It is represented by equation (4).

[0065] [Mathematical Expression 4]

[0066]

[0067] Here, if we consider the actual interlayer spacing λ for equation (4) t The distribution G(λ) t If the apparent interlayer spacing λ is... a The distribution is shown in equation (a). Here, we assume the actual interlayer spacing λ. t The distribution G(λ) t The distribution is normally distributed.

[0068] By using equation (a) to calculate the apparent interlayer spacing λ of the surface region a The distribution is fitted to obtain the true interlayer spacing λ. t The average value of LaveS(nm) (=B), the true interlayer spacing λ t The maximum value LmaxS(nm) (=B+2.33C), the true interlayer spacing λ t The half-width of the distribution, FWHMs (=2.35×C). Similarly, by using Equation (a), the apparent interlayer spacing λ of the central region is... a The distribution is fitted to obtain the true interlayer spacing λ. t The half-width of the distribution is FWHMc.

[0069] The distribution of interlayer spacing obtained by the above method and its relationship with the reduction of area value obtained by tensile testing of wire were investigated. The results yielded the following insights: the interlayer spacing obtained by the above method (the true interlayer spacing λ) tThe sharper the distribution of interlayer spacing, that is, the narrower the distribution range of interlayer spacing, the higher the cross-sectional reduction rate. Through further research, the inventors found that in a circular cross-section perpendicular to the axial direction of the wire, when the average interlayer spacing at a depth of 0.5 mm from the wire surface is set as LaveS (nm) and the maximum interlayer spacing as LmaxS (nm), if LmaxS / LaveS is below 1.70, the wire drawing processability is improved.

[0070] However, even wires that meet the above chemical composition and have an LmaxS / LaveS ratio of 1.70 or less still cannot achieve excellent wire drawing properties. Therefore, the inventors conducted further research. As a result, the following insights were obtained.

[0071] In the surface layer of a circular cross-section perpendicular to the wire axis, as mentioned above, the narrower the interlayer spacing, the better the wire drawing processability. However, in the center of a circular cross-section perpendicular to the wire axis, superior processing and curing properties are obtained when the interlayer spacing is relatively wide. The reason for this is not yet determined, but the following reasons can be considered.

[0072] During wire drawing, strain is introduced into the surface layer of the wire. This causes surface solidification. To improve wire drawing processability, it is preferable that the solidification process is uniformly applied within a circular cross-section. If the solidification process is uneven, hardness variations will occur within the circular cross-section. In this case, localized cracking can occur and propagate from areas of lower hardness within the circular cross-section, leading to fracture. On the other hand, if the solidification process is uniform, hardness variations within the circular cross-section are less likely to occur. This suppresses the formation of localized cracks, resulting in improved wire drawing processability.

[0073] To ensure uniform curing in a circular cross-section, it is effective to have a wider interlayer spacing distribution in the central region than in the surface region. In other words, it is effective to have a larger interlayer spacing deviation in the central region compared to the surface region. In this case, curing of the surface layer tends to proceed towards the central region, resulting in a more uniform hardness distribution throughout the circular cross-section. Consequently, excellent wire drawing properties are achieved in the wire.

[0074] Based on the above insights, the inventors investigated the relationship between the interlayer spacing distribution in the surface region and the interlayer spacing distribution in the central region of a circular cross-section and its wire drawing processability. The results showed that, in a circular cross-section, when the half-width of the interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-width of the interlayer spacing at the center of the wire is set as FWHMc (nm), excellent wire drawing processability can be obtained if FWHMc / FWHMs is 1.10~2.00.

[0075] It should be noted that, through steps 1 to 3, even if... Figure 5 The small segments 30 with a ratio NR exceeding 50% as shown are not considered as the measurement objects. Figure 4 and Figure 6 When the number of small segments 30 with a ratio NR of less than 50% as shown is used as the measurement object, the true interlayer spacing λ in the obtained surface region is... t The average value of LaveS (nm), the maximum value of LmaxS (nm), the full width at half maximum (FWHMs) (nm), and the true interlayer spacing λ in the central region. t The half-width full width FWHMc (nm) also shows a good correlation with wire drawing processability.

[0076] The essence of the wire of the present invention, based on the above insights, is as follows.

[0077] The chemical composition of the wire in component 1, by mass%, contains: C: 0.70~1.20%, Si: 0.10~1.50%, Mn: 0.10~1.00%, P: less than 0.020%, S: less than 0.020%, Al: less than 0.080%, N: 0.0010~0.0100%, O: less than 0.0050%, Cr: 0~0.50%, Co: 0~0.50%, Cu: 0~0.50%, Ni: 0~0.50%. The composition is as follows: Mo: 0~0.20%, B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, As: 0~0.050%, Sb: 0~0.050%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%, with the balance consisting of Fe and impurities. Furthermore, in a circular cross-section perpendicular to the wire axis, when the average value of the actual interlayer spacing at a depth of 0.5 mm from the wire surface is defined as LaveS (nm) and the maximum value of the actual interlayer spacing is defined as LmaxS (nm), the ratio LmaxS / LaveS is less than 1.70. In a circular cross-section, when the half-value full width of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-value full width of the actual interlayer spacing at the center of the wire is set as FWHMc (nm), the ratio of FWHMc / FWHMs is 1.10~2.00.

[0078] The second type of wire, in the first type of wire, contains, by mass percent, one or more of the following: Cr: 0.01-0.50%, Co: 0.01-0.50%, Cu: 0.01-0.50%, Ni: 0.01-0.50%, Mo: 0.01-0.20%, B: 0.001-0.005%, W: 0.01-0.20%, Ti: 0.01-0.10%, Nb: 0.01-0.10%, Sn: 0.01-0.10%, As: 0.001-0.050%, Sb: 0.001-0.050%, and V: 0.01-0.10%.

[0079] The chemical composition of the wire in the third component, by mass%, contains: C: 0.70~1.20%, Si: 0.10~1.50%, Mn: 0.10~1.00%, P: less than 0.020%, S: less than 0.020%, Al: less than 0.080%, N: 0.0010~0.0100%, O: less than 0.0050%, Cr: 0~0.50%, Co: 0~0.50%, Cu: 0~0.5%. The composition is as follows: Ni: 0~0.50%, Mo: 0~0.20%, B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%, with the balance consisting of Fe and impurities. Furthermore, in a circular cross-section perpendicular to the wire's axis, when the average value of the actual interlayer spacing at a depth of 0.5 mm from the wire surface is defined as LaveS (nm) and the maximum value of the actual interlayer spacing is defined as LmaxS (nm), the ratio LmaxS / LaveS is less than 1.70. In a circular cross-section, when the half-value full width of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-value full width of the actual interlayer spacing at the center of the wire is set as FWHMc (nm), the ratio of FWHMc / FWHMs is 1.10~2.00.

[0080] The fourth type of wire, in the third type of wire, contains, by mass percent, one or more of the following: Cr: 0.01-0.50%, Co: 0.01-0.50%, Cu: 0.01-0.50%, Ni: 0.01-0.50%, Mo: 0.01-0.20%, B: 0.001-0.005%, W: 0.01-0.20%, Ti: 0.01-0.10%, Nb: 0.01-0.10%, Sn: 0.01-0.10%, and V: 0.01-0.10%.

[0081] The fifth type of wire, in the first to fourth types of wire, has a chemical composition, by mass%, containing one or more of the following groups: Ca: 0.0001 to 0.0050%, Mg: 0.0001 to 0.0050%, Zr: 0.001 to 0.010%, and rare earth elements: 0.0001 to 0.0050%.

[0082] The wire of this embodiment will now be described in detail. It should be noted that, unless otherwise specified, "%" related to elements refers to mass%.

[0083] [Features of the wire in this embodiment]

[0084] The wire in this embodiment includes the following features 1 to 3.

[0085] (Feature 1)

[0086] The chemical composition, by mass%, contains: C: 0.70–1.20%, Si: 0.10–1.50%, Mn: 0.10–1.00%, P: less than 0.020%, S: less than 0.020%, Al: less than 0.080%, N: 0.0010–0.0100%, O: less than 0.0050%, Cr: 0–0.50%, Co: 0–0.50%, Cu: 0–0.50%, Ni: 0–0.50%, Mo… : 0~0.20%, B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, As: 0~0.050%, Sb: 0~0.050%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%, with the balance consisting of Fe and impurities.

[0087] (Feature 2)

[0088] In a circular cross-section perpendicular to the wire axis, when the average value of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as LaveS (nm) and the maximum value of the actual interlayer spacing is set as LmaxS (nm), LmaxS / LaveS is less than 1.70.

[0089] (Feature 3)

[0090] In a circular cross-section, when the half-value full width of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-value full width of the actual interlayer spacing at the center of the wire is set as FWHMc (nm), the ratio of FWHMc / FWHMs is 1.10~2.00.

[0091] The following describes features 1 through 3.

[0092] [Regarding (Characteristic 1) Chemical Composition]

[0093] The chemical composition of the wire in this embodiment contains the following elements.

[0094] C: 0.70~1.20%

[0095] Carbon (C) improves the strength of the wire. When the C content is less than 0.70%, even if the contents of other elements are within the range of this embodiment, the above-mentioned effect cannot be fully obtained.

[0096] On the other hand, if the carbon content exceeds 1.20%, excessive formation of primary cementite will occur even if the contents of other elements are within the range of this embodiment. In this case, the wire drawing processability is reduced.

[0097] Therefore, the C content is 0.70~1.20%.

[0098] The preferred lower limit for C content is 0.72%, further preferably 0.78%, further preferably 0.80%, and further preferably 0.82%.

[0099] The preferred upper limit for C content is 1.18%, more preferably 1.12%, more preferably 1.08%, and more preferably 1.05%.

[0100] Si: 0.10~1.50%

[0101] Silicon (Si) improves the strength of the wire. Si is also used in the steelmaking process of the wire manufacturing process to deacidify the steel. If the Si content is less than 0.10%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.

[0102] On the other hand, if the Si content exceeds 1.50%, Si will segregate within the wire rod, the raw material for steel wire, even if the contents of other elements are within the range of this embodiment. In this case, bainite is formed in the region where Si segregation occurs, reducing the wire's workability.

[0103] Therefore, the Si content is 0.10~1.50%.

[0104] The preferred lower limit for Si content is 0.15%, more preferably 0.20%, and even more preferably 0.25%.

[0105] The preferred upper limit for Si content is 1.42%, more preferably 1.35%, more preferably 1.00%, more preferably 0.90%, and more preferably 0.80%.

[0106] Mn: 0.10~1.00%

[0107] Manganese (Mn) improves the hardenability of steel and increases the strength of wire. Mn also fixes sulfur in the steel, improving the hot workability of the wire. If the Mn content is less than 0.10%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of this embodiment.

[0108] On the other hand, if the Mn content exceeds 1.00%, Mn will still segregate within the wire even if the contents of other elements are within the range of this embodiment. In this case, bainite is formed in the region where Mn segregation has occurred, reducing the wire's workability.

[0109] Therefore, the Mn content is 0.10~1.00%.

[0110] The preferred lower limit for Mn content is 0.12%, more preferably 0.20%, and even more preferably 0.25%.

[0111] The preferred upper limit for Mn content is 0.90%, more preferably 0.85%, more preferably 0.80%, and more preferably 0.70%.

[0112] P: below 0.020%

[0113] Phosphorus (P) is an impurity. If the P content exceeds 0.020%, P will segregate at the grain boundaries even if the contents of other elements are within the range of this embodiment. Therefore, grain boundary embrittlement leads to a decrease in the wire drawing processability.

[0114] Therefore, the P content is below 0.020%.

[0115] The phosphorus (P) content should ideally be as low as possible. However, excessive reduction in P content can lead to increased manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for P content is more than 0%, more preferably 0.001%, more preferably 0.003%, and more preferably 0.005%.

[0116] The preferred upper limit for the P content is 0.018%, more preferably 0.016%, and even more preferably 0.015%.

[0117] S: below 0.020%

[0118] Sulfur (S) is an impurity. If the S content exceeds 0.020%, S will segregate at the grain boundaries even if the contents of other elements are within the range of this embodiment. In addition, coarse MnS will be excessively generated. Therefore, the wire drawing processability is reduced.

[0119] Therefore, the sulfur content is below 0.020%.

[0120] The sulfur (S) content should ideally be as low as possible. However, excessive reduction in S content can lead to increased manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for S content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%.

[0121] The preferred upper limit for the sulfur content is 0.018%, more preferably 0.016%, more preferably 0.014%, more preferably 0.010%, and more preferably 0.008%.

[0122] Al: below 0.080%

[0123] Aluminum (Al) deacidifies steel. Even small amounts of Al can achieve the aforementioned effect to some extent. However, if the Al content exceeds 0.080%, coarse oxides will be excessively formed, even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability decreases.

[0124] Therefore, the Al content is below 0.080%.

[0125] The preferred lower limit for Al content is more than 0%, more preferably 0.001%, more preferably 0.003%, and more preferably 0.0007%.

[0126] The preferred upper limit for Al content is 0.075%, more preferably 0.070%, more preferably 0.065%, and more preferably 0.0060%.

[0127] N: 0.0010~0.0100%

[0128] During the wire drawing process, nitrogen (N) fixes dislocations, thereby increasing the strength of the drawn steel wire. If the N content is less than 0.0010%, the above-mentioned effect cannot be fully obtained even if the contents of other elements are within the range of this embodiment.

[0129] On the other hand, if the nitrogen content exceeds 0.0100%, excessive nitride formation will occur in the wire even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0130] Therefore, the N content is 0.0010~0.0100%.

[0131] The preferred lower limit for N content is 0.0015%, more preferably 0.0020%, and even more preferably 0.0025%.

[0132] The preferred upper limit for N content is 0.0090%, more preferably 0.0080%, more preferably 0.0070%, and more preferably 0.0060%.

[0133] O: Below 0.0050%

[0134] Oxygen (O) is an impurity. If the O content exceeds 0.0050%, coarse oxides will be excessively generated in the wire, even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0135] Therefore, the O content is below 0.0050%.

[0136] Ideally, the oxygen content should be as low as possible. However, excessive reduction in oxygen content can lead to increased manufacturing costs. Therefore, considering typical industrial production, the preferred lower limit for oxygen content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and more preferably 0.0005%.

[0137] The preferred upper limit for the O content is 0.0045%, more preferably 0.0040%, more preferably 0.0030%, and more preferably 0.0020%.

[0138] The remaining chemical composition of the wire in this embodiment consists of Fe and impurities. Here, impurities in the chemical composition refer to substances that are introduced into the wire during industrial manufacturing from raw materials such as ores, waste, or the manufacturing environment, but are not intentionally present. Such impurities are permissible as long as they do not adversely affect the wire of this embodiment.

[0139] [About Optional Elements]

[0140] The chemical composition of the wire in this embodiment may further contain one or more elements selected from the group consisting of Fe, replacing a portion of Fe: Cr: 0~0.50%, Co: 0~0.50%, Cu: 0~0.50%, Ni: 0~0.50%, Mo: 0~0.20%, B: 0~0.005%, W: 0~0.20%, Ti: 0~0.10%, Nb: 0~0.10%, Sn: 0~0.10%, As: 0~0.050%, Sb: 0~0.050%, V: 0~0.10%, Ca: 0~0.0050%, Mg: 0~0.0050%, Zr: 0~0.010%, and rare earth elements: 0~0.0050%. These elements are arbitrary. The descriptions of each arbitrary element are as follows.

[0141] [Group 1: Cr, Co, Cu, Ni, Mo, B, W, Ti, Nb, Sn, As, Sb, and V]

[0142] The chemical composition of the wire in this embodiment may further contain one or more elements selected from the group consisting of: Cr, Co, Cu, Ni, Mo, B, W, Ti, Nb, Sn, As, Sb, and V. These elements are arbitrary and all improve the hardenability of the steel.

[0143] Cr: 0~0.50%

[0144] Chromium (Cr) can be any element, or it can be absent. That is to say, the Cr content can be 0%.

[0145] When Cr is present, meaning the Cr content exceeds 0%, Cr improves the hardenability of steel and increases the strength of wire. Even a small amount of Cr can achieve these effects to some extent.

[0146] However, if the Cr content exceeds 0.50%, Cr will still segregate within the wire even if the contents of other elements are within the range of this embodiment. In this case, bainite will form in the regions where Cr segregation has occurred, reducing the wire's workability.

[0147] Therefore, the Cr content is 0~0.50%.

[0148] The preferred lower limit for Cr content is 0.01%, more preferably 0.05%, and even more preferably 0.08%.

[0149] The preferred upper limit for Cr content is 0.45%, more preferably 0.40%, more preferably 0.35%, and more preferably 0.30%.

[0150] Co: 0~0.50%

[0151] Cobalt (Co) can be any element, or it can be absent. That is to say, the Co content can be 0%.

[0152] When present in a presence, that is, when the Co content exceeds 0%, Co improves the hardenability of steel and increases the strength of wire. Even a small amount of Co can achieve the above effects to some extent.

[0153] However, if the Co content exceeds 0.50%, the wire hardness will become excessively high, even if the contents of other elements are within the range of this embodiment, and the wire's drawability will decrease.

[0154] Therefore, the Co content is 0~0.50%.

[0155] The preferred lower limit for the Co content is 0.01%, more preferably 0.05%, and even more preferably 0.08%.

[0156] The preferred upper limit for the Co content is 0.45%, more preferably 0.40%, more preferably 0.35%, more preferably 0.30%, and more preferably 0.20%.

[0157] Cu: 0~0.50%

[0158] Copper (Cu) can be any element, or it can be absent. In other words, the Cu content can be 0%.

[0159] When present in a Cu concentration, meaning when the Cu content exceeds 0%, Cu improves the hardenability of steel and increases the strength of the wire. Even a small amount of Cu can achieve these effects to some extent.

[0160] However, if the Cu content exceeds 0.50%, the wire hardness will become excessively high, even if the contents of other elements are within the range of this embodiment, and the wire's drawability will decrease.

[0161] Therefore, the Cu content is 0~0.50%.

[0162] The preferred lower limit for Cu content is 0.01%, more preferably 0.05%, more preferably 0.08%, and more preferably 0.15%.

[0163] The preferred upper limit for Cu content is 0.45%, more preferably 0.40%, more preferably 0.35%, more preferably 0.30%, and more preferably 0.25%.

[0164] Ni: 0~0.50%

[0165] Nickel (Ni) can be any element, or it can be absent. That is to say, the Ni content can be 0%.

[0166] In the presence of Ni, that is, when the Ni content exceeds 0%, Ni improves the hardenability of steel. Ni also delays the phase transformation of primary cementite and grain boundary ferrite during the cooling process from the austenitic temperature range in wire manufacturing. This allows for the formation of a fine pearlite layer. As a result, the wire's workability is well maintained, and the strength of steel wire manufactured from it is increased. Even a small amount of Ni can achieve these effects to some extent.

[0167] However, if the Ni content exceeds 0.50%, the hardenability of the steel increases excessively. In this case, even if the contents of other elements are within the range of this embodiment, bainite will form in the wire, reducing the wire's workability.

[0168] Therefore, the Ni content is 0~0.50%.

[0169] The preferred lower limit for Ni content is 0.01%, more preferably 0.05%, and even more preferably 0.08%.

[0170] The preferred upper limit for Ni content is 0.45%, more preferably 0.40%, more preferably 0.35%, more preferably 0.30%, and more preferably 0.25%.

[0171] Mo: 0~0.20%

[0172] Molybdenum (Mo) can be any element, or it can be absent. That is to say, the Mo content can be 0%.

[0173] When present in a Mo concentration exceeding 0%, Mo improves the hardenability and strength of the wire. Even a small amount of Mo can achieve these effects to some extent.

[0174] However, if the Mo content exceeds 0.20%, the hot workability of the steel will decrease during the wire manufacturing process, even if the contents of other elements are within the range of this embodiment.

[0175] Therefore, the Mo content is 0~0.20%.

[0176] The preferred lower limit for the Mo content is 0.01%, more preferably 0.03%, and even more preferably 0.05%.

[0177] The preferred upper limit for the Mo content is 0.18%, more preferably 0.16%, more preferably 0.14%, more preferably 0.12%, and more preferably 0.10%.

[0178] B: 0~0.005%

[0179] Boron (B) can be any element, or it can be absent. That is to say, the B content can be 0%.

[0180] When present in a substance, specifically when the boron content exceeds 0%, boron improves the hardenability and strength of the wire. Even a small amount of boron can achieve these effects to some extent.

[0181] However, if the B content exceeds 0.005%, the hot workability of the steel will decrease during the wire manufacturing process, even if the contents of other elements are within the range of this embodiment.

[0182] Therefore, the content of B is 0~0.005%.

[0183] The preferred lower limit for the B content is 0.001%, and more preferably 0.002%.

[0184] The preferred upper limit for the B content is 0.004%, more preferably 0.003%, and even more preferably 0.002%.

[0185] W: 0~0.20%

[0186] Tungsten (W) can be any element, or it can be absent. That is to say, the W content can be 0%.

[0187] When present in a W content, meaning exceeding 0%, W improves the hardenability and strength of the wire. Even a small amount of W can achieve these effects to some extent.

[0188] However, if the W content exceeds 0.20%, the hot workability of the steel will decrease during the wire manufacturing process, even if the contents of other elements are within the range of this embodiment.

[0189] Therefore, the W content is 0~0.20%.

[0190] The preferred lower limit for W content is 0.01%, more preferably 0.03%, more preferably 0.05%, and more preferably 0.08%.

[0191] The preferred upper limit for W content is 0.18%, more preferably 0.16%, more preferably 0.14%, more preferably 0.12%, and more preferably 0.10%.

[0192] Ti: 0~0.10%

[0193] Titanium (Ti) can be any element, or it can be absent. In other words, the Ti content can be 0%.

[0194] When Ti is present, meaning its content exceeds 0%, it improves the hardenability and strength of the wire. Even a small amount of Ti can achieve these effects to some extent.

[0195] However, if the Ti content exceeds 0.10%, the hot workability of the steel will decrease during the wire manufacturing process, even if the contents of other elements are within the range of this embodiment.

[0196] Therefore, the Ti content is 0~0.10%.

[0197] The preferred lower limit for Ti content is 0.01%, more preferably 0.02%, and even more preferably 0.03%.

[0198] The preferred upper limit for Ti content is 0.09%, more preferably 0.08%, more preferably 0.07%, and more preferably 0.05%.

[0199] Nb: 0~0.10%

[0200] Nickel (Nb) can be any element, or it can be absent. That is to say, the Nb content can be 0%.

[0201] When present in a concentration of Nb, meaning when the Nb content exceeds 0%, Nb improves the hardenability and strength of the wire. Even a small amount of Nb can achieve these effects to some extent.

[0202] However, if the Nb content exceeds 0.10%, the hot workability of the steel will decrease during the wire manufacturing process, even if the contents of other elements are within the range of this embodiment.

[0203] Therefore, the Nb content is 0~0.10%.

[0204] The preferred lower limit for Nb content is 0.01%, more preferably 0.02%, and even more preferably 0.03%.

[0205] The preferred upper limit for Nb content is 0.09%, more preferably 0.08%, more preferably 0.07%, and more preferably 0.05%.

[0206] Sn: 0~0.10%

[0207] Tin (Sn) can be any element, or it can be absent. That is to say, the Sn content can be 0%.

[0208] When Sn is present, that is, when the Sn content exceeds 0%, Sn inhibits ferrite decarburization during hot working and suppresses the reduction in wire strength. Even a small amount of Sn can achieve the above-mentioned effect to some extent.

[0209] However, if the Sn content exceeds 0.10%, Sn will segregate at grain boundaries and cause red-hot embrittlement, even if the contents of other elements are within the range of this embodiment. In this case, the hot workability of the wire is reduced.

[0210] Therefore, the Sn content is 0~0.10%.

[0211] The preferred lower limit for Sn content is 0.01%, more preferably 0.02%, and even more preferably 0.03%.

[0212] The preferred upper limit for Sn content is 0.09%, more preferably 0.08%, and even more preferably 0.07%.

[0213] As: 0~0.050%

[0214] Arsenic (As) can be any element, or it can be absent. That is to say, the As content can be 0%.

[0215] When present in a concentration of asperium (As), specifically when the As content exceeds 0%, it increases the strength of the wire. Even a small amount of As can achieve the aforementioned effect to some extent.

[0216] However, if the As content exceeds 0.050%, the thermal workability of the wire will decrease even if the contents of other elements are within the range of this embodiment.

[0217] Therefore, the As content is 0~0.050%.

[0218] The preferred lower limit for the As content is 0.001%, more preferably 0.005%, and even more preferably 0.010%.

[0219] The preferred upper limit for the As content is 0.049%, more preferably 0.040%, and even more preferably 0.030%.

[0220] Sb: 0~0.050%

[0221] Antimony (Sb) can be any element, or it can be absent. That is to say, the Sb content can be 0%.

[0222] When present in a concentration of Sb, meaning when the Sb content exceeds 0%, Sb increases the strength of the wire. Even a small amount of Sb can achieve the aforementioned effect to some extent.

[0223] However, if the Sb content exceeds 0.050%, the thermal workability of the wire will decrease even if the contents of other elements are within the range of this embodiment.

[0224] Therefore, the Sb content is 0~0.050%.

[0225] The preferred lower limit for Sb content is 0.001%, more preferably 0.005%, and even more preferably 0.010%.

[0226] The preferred upper limit for Sb content is 0.049%, more preferably 0.040%, and even more preferably 0.030%.

[0227] V: 0~0.10%

[0228] Vanadium (V) can be any element, or it can be absent. That is to say, the V content can be 0%.

[0229] When present in a V content exceeding 0%, V improves the hardenability and strength of the wire. Even a small amount of V can achieve these effects to some extent.

[0230] However, if the V content exceeds 0.10%, the wire drawing processability will decrease even if the contents of other elements are within the range of this embodiment.

[0231] Therefore, the V content is 0~0.10%.

[0232] The preferred lower limit for V content is 0.01%, more preferably 0.02%, and even more preferably 0.03%.

[0233] The preferred upper limit for V content is 0.09%, more preferably 0.08%, and even more preferably 0.07%.

[0234] [Group 2: Ca, Mg, Zr and Rare Earth Elements (REM)]

[0235] The chemical composition of the wire in this embodiment may further include one or more elements selected from the group consisting of Ca, Mg, Zr, and rare earth elements (REM). These elements are arbitrary and all improve the ductility of the wire.

[0236] Ca: 0~0.0050%

[0237] Calcium (Ca) can be any element, or it can be absent. In other words, the Ca content can be 0%.

[0238] When present in a calcium-containing state, meaning when the calcium content exceeds 0%, calcium reduces hard alumina inclusions and improves the ductility of the wire. Even a small amount of calcium can achieve the above effects to some extent.

[0239] However, if the Ca content exceeds 0.0050%, coarse oxides will be excessively generated even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0240] Therefore, the Ca content is 0~0.0050%.

[0241] The preferred lower limit for Ca content is 0.0001%, more preferably 0.0005%, and even more preferably 0.0008%.

[0242] The preferred upper limit for Ca content is 0.0045%, more preferably 0.0040%, more preferably 0.0035%, more preferably 0.0030%, more preferably 0.0025%, and more preferably 0.0020%.

[0243] Mg: 0~0.0050%

[0244] Magnesium (Mg) can be any element, or it can be absent. In other words, the Mg content can be 0%.

[0245] In the presence of Mg, specifically when the Mg content exceeds 0%, Mg forms fine oxides. These fine oxides refine the wire's structure, improving its ductility. Even a small amount of Mg can achieve these effects to some extent.

[0246] However, if the Mg content exceeds 0.0050%, coarse oxides will be excessively generated even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0247] Therefore, the Mg content is 0~0.0050%.

[0248] The preferred lower limit for Mg content is 0.0001%, more preferably 0.0005%, and even more preferably 0.0008%.

[0249] The preferred upper limit for Mg content is 0.0045%, more preferably 0.0040%, more preferably 0.0035%, more preferably 0.0030%, and more preferably 0.0025%.

[0250] Zr: 0~0.010%

[0251] Zirconium (Zr) can be any element, or it can be absent. That is to say, the Zr content can be 0%.

[0252] In the presence of Zr, that is, when the Zr content exceeds 0%, Zr forms fine oxides. These fine oxides refine the wire's structure, improving its ductility. Even a small amount of Zr can achieve these effects to some extent.

[0253] However, if the Zr content exceeds 0.010%, coarse oxides will be excessively generated even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0254] Therefore, the Zr content is 0~0.010%.

[0255] The preferred lower limit for Zr content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.

[0256] The preferred upper limit for Zr content is 0.009%, more preferably 0.008%, and even more preferably 0.007%.

[0257] Rare earth elements: 0~0.0050%

[0258] Rare earth elements (REM) can be any element, or they can be absent. In other words, the REM content can be 0%.

[0259] When REM is present, meaning the REM content exceeds 0%, it forms fine sulfides, thus neutralizing sulfur. This improves the wire's ductility. Even a small amount of REM can achieve these effects to some extent.

[0260] However, if the REM content exceeds 0.0050%, coarse oxides will be excessively generated even if the contents of other elements are within the range of this embodiment. In this case, the wire's drawability is reduced.

[0261] Therefore, the REM content is 0~0.0050%.

[0262] The preferred lower limit for REM content is 0.0001%, more preferably 0.0005%, more preferably 0.0008%, more preferably 0.0013%, and more preferably 0.0018%.

[0263] The preferred upper limit for REM content is 0.0045%, more preferably 0.0040%, more preferably 0.0035%, and more preferably 0.0030%.

[0264] In this specification, REM refers to one or more elements selected from scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, which are lanthanide elements. Furthermore, the REM content in this specification refers to the total content of these elements.

[0265] [Regarding (Feature 2) LmaxS / LaveS]

[0266] In the wire of this embodiment, furthermore, in the circular cross-section perpendicular to the axial direction of the wire, when the average value of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as LaveS (nm) and the maximum value of the actual interlayer spacing is set as LmaxS (nm), LmaxS / LaveS is 1.70 or less. If LmaxS / LaveS is 1.70 or less on the surface of the wire, the wire's drawability is improved.

[0267] The preferred upper limit for LmaxS / LaveS is 1.65, more preferably 1.60, more preferably 1.55, and more preferably 1.50.

[0268] The lower bound of LmaxS / LaveS is not specifically defined. The lower bound of LmaxS / LaveS is, for example, 1.20, 1.10, or 1.00.

[0269] [Regarding (Feature 3) FWHMc / FWHMs]

[0270] In the wire of this embodiment, further, in the circular cross-section, when the half-value full width of the actual interlayer spacing at a depth of 0.5 mm from the surface of the wire is set as FWHMs (nm) and the half-value full width of the actual interlayer spacing at the center of the wire is set as FWHMc (nm), FWHMc / FWHMs is 1.10~2.00.

[0271] If FWHMc / FWHMs is 1.10~2.00, the interlayer spacing distribution in the central region of the circular cross-section of the wire is sufficiently wider than that in the surface layer. Therefore, surface curing tends to proceed towards the center, resulting in a more uniform hardness distribution within the circular cross-section. Consequently, the wire's drawability is improved.

[0272] The preferred lower limit for FWHMc / FWHMs is 1.12, more preferably 1.15, more preferably 1.20, and more preferably 1.25.

[0273] The preferred upper limit for FWHMc / FWHMs is 1.90, further preferably 1.80, further preferably 1.70, and further preferably 1.65.

[0274] [Methods for determining LaveS, LmaxS, FWHMc, and FWHMs]

[0275] LaveS, LmaxS, FWHMc, and FWHMs can be achieved by implementing the above [regarding the true interlayer spacing λ]. t The distribution is determined by steps 1 to 3 of the method for determining the distribution.

[0276] [Effects of the wire in this embodiment]

[0277] The wire of this embodiment satisfies features 1 to 3. Therefore, in the wire of this embodiment, excellent wire drawing processability is obtained by limiting the distribution of interlayer spacing.

[0278] [Microstructure of the wire in this embodiment]

[0279] In the microstructure of the wire of this embodiment, the pearlite area fraction is 95% or more. That is, the microstructure of the wire of this embodiment is substantially composed of pearlite. In the microstructure, the microstructure other than pearlite is composed of one or more selected from ferrite, primary cementite, bainite and martensite.

[0280] [Method for determining pearlite area ratio]

[0281] The pearlite area ratio in the microstructure of the wire in this embodiment was determined by the following method.

[0282] A test piece was prepared with a cross-section parallel to the central axis of the wire as the observation surface. The observation surface of the test piece was mirror-polished. Within 5 minutes after mirror polishing, the observation surface was etched using Picral for approximately 7 seconds to reveal the microstructure. Four rectangular fields of view, each 50 μm radially and 40 μm axially, were selected within the etched observation surface, encompassing the central axis of the wire. These four fields of view were arranged with an axial spacing of 100 μm. It should be noted that the central axis of the wire was positioned at the radial center of each field of view.

[0283] For each field of view, observations were performed using a field emission scanning electron microscope (FE-SEM) at a magnification of 2000x to generate photographic images.

[0284] Pearlite and other microstructures (ferrite, primary cementite, bainite, and martensite) are determined based on the contrast and morphology of photographic images from each field of view. Within the field of view, a striped pattern consisting of low-brightness black ferrite and high-brightness white cementite is identified as pearlite. Distinguishing between microstructures other than pearlite is not necessary, but regions with black grains where no substructure is observed within the grain are considered ferrite.

[0285] The pearlite area ratio (%) is calculated based on the total area of ​​pearlites identified in four observation fields and the total area of ​​the four observation fields. The pearlite area ratio (%) is set as an integer obtained by rounding the first decimal place of the obtained value.

[0286] [Applications of the wires applicable to this embodiment]

[0287] The wire described in this embodiment can be widely used as a raw material for steel wire manufactured through wire drawing. The steel wire can be used for applications such as tire wire, steel cord, bridge wire, and steel rope.

[0288] [The cross-sectional shape of the wire perpendicular to the axial direction in this embodiment]

[0289] The cross-section of the wire in this embodiment, perpendicular to the axial direction, is, for example, circular. The wire diameter of this embodiment is not particularly limited. The wire diameter is, for example, 3.0 to 8.0 mm. It should be noted that the diameter of the steel wire manufactured using the wire of this embodiment as raw material is, for example, 0.8 to 3.0 mm. It should be noted that the term "circular shape" as used above includes not only a perfect circle, but also a circular shape that satisfies, for example, the off-diameter difference (0.64 mm or less) specified in Table 3 of JIS G 3506 (2017) "Hard Steel Wire" 7.b).

[0290] [An example of the wire manufacturing method of this embodiment]

[0291] An example of a method for manufacturing the wire according to this embodiment will be described. The method for manufacturing the wire described below is an example for manufacturing the wire according to this embodiment. Therefore, the wire having the above-described structure can also be manufactured by other manufacturing methods besides the method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing the wire according to this embodiment.

[0292] An example of the wire manufacturing method of this embodiment includes the following steps.

[0293] (Process 1) Raw material preparation process

[0294] (Process 2) Billet rolling process

[0295] (Process 3) Finishing rolling process

[0296] The following is a description of each process.

[0297] [(Process 1) Raw material preparation process]

[0298] In the raw material preparation process, the raw materials for the wire rod of this embodiment are prepared. Specifically, molten steel with a chemical composition satisfying characteristic 1 is manufactured. The refining method is not particularly limited, and a known method can be used. For example, the molten iron produced by the known method is refined in a converter (primary refining). The molten steel tapped from the converter is then refined using a known secondary refining process. Through the above processes, molten steel with a chemical composition satisfying characteristic 1 is manufactured.

[0299] Using molten steel, raw materials are manufactured through well-known casting methods. For example, molten steel can be used to manufacture steel ingots (ingots) through casting. Alternatively, molten steel can be used to manufacture steel blocks (blooms) through continuous casting. Raw materials (steel ingots or steel blocks) are manufactured through these methods.

[0300] [(Process 2) Billet rolling process]

[0301] In the billet rolling process, the raw materials (steel ingots or steel blocks) prepared in the raw material preparation process are rolled to produce steel billets.

[0302] In the billet rolling process, the raw material is first heated in a furnace using well-known methods. There are no particular limitations on the heating temperature; any well-known temperature will suffice. For example, a heating temperature of 1000~1200℃ is acceptable.

[0303] Steel billets are manufactured by hot rolling (rough rolling) heated raw materials using a roughing mill, or a roughing mill and a continuous rolling mill. Specifically, steel billets are manufactured by reverse rolling heated raw materials using a roughing mill. When a well-known continuous rolling mill is located downstream of the roughing mill, the steel billets after roughing can be further rolled in series using the continuous rolling mill to manufacture smaller steel billets.

[0304] The cooling conditions for the hot-rolled steel billet in the billet rolling process are as follows.

[0305] (Condition 1) Set the cooling rate at 700~670℃ to below 0.50℃ / second.

[0306] In the billet rolling process, pearlite is formed in the billet within a temperature range of 700–670°C after hot rolling. If the cooling rate at 700–670°C exceeds 0.50°C / second, the cooling rate is too fast. In this case, the difference in interlayer spacing between the pearlite in the central region and the pearlite in the surface region of the manufactured wire is not significant. As a result, FWHMc / FWHMs is less than 1.10.

[0307] If the cooling rate in the billet rolling process (700-670℃) is set to a slow cooling of less than 0.50℃ / second, Mn segregation (center segregation) will moderately form in the center of the billet. Through this center segregation, the actual interlayer spacing λ in the central region of the wire rod during the finishing rolling process will be significantly reduced. t Increase, interlayer spacing λ t The distribution widens. As a result, FWHMc / FWHMs reaches an appropriate range.

[0308] [(Process 3) Finish rolling process]

[0309] In the finishing rolling process, steel billets manufactured in the roughing rolling process are finished rolled to produce wire rod. The finishing rolling process includes the following steps.

[0310] (Process 31) Heating Process

[0311] (Process 32) Rolling process

[0312] The heating and rolling processes in the finishing rolling process are described below.

[0313] [(Process 31) Heating Process]

[0314] In the heating process, a heating furnace is used to heat the steel billet manufactured in the billet rolling process. The heating temperature is set to 900~1150℃.

[0315] [(Process 32) Rolling process]

[0316] In the rolling process, wire rod is manufactured by finishing the steel billet, which has been heated in the heating process, using a continuous rolling mill. A continuous rolling mill consists of multiple rolling stands arranged in a row from upstream to downstream. Each rolling stand contains a pair of work rolls. Grooves are formed on each work roll, and a pass is formed through the grooves of the pair of work rolls.

[0317] In the rolling process, the following conditions must be further met.

[0318] (Condition 2) Set the finishing rolling temperature to 910~1150℃.

[0319] (Condition 3) Water cooling shall begin within 0.5 seconds after the final finishing rolling is completed.

[0320] The following explains conditions 2 and 3.

[0321] [Regarding (Condition 2) Finishing temperature]

[0322] As mentioned above, finishing rolling temperature refers to the surface temperature (°C) of the steel (wire) at the entry side of the rolling mill stand after the steel has undergone its final reduction using a continuous rolling mill. Finishing rolling temperature can be measured using a thermometer installed at the entry side of the rolling mill stand after the final reduction has been applied.

[0323] If the finishing rolling temperature is 910~1150℃, then the actual interlayer spacing λ in the central region of the finished steel billet is... t It will not change significantly due to finishing rolling. Therefore, it can maintain the true interlayer spacing λ in the central region. t A state with large deviation.

[0324] [Regarding (Condition 3) Water cooling immediately after the final finishing rolling]

[0325] In the wire rod immediately after final finishing rolling, the austenite grains in the surface layer with high strain undergo further refinement. However, if the high-temperature condition continues, the austenite grains in the surface layer grow, while the austenite grains in the axial cross-section of the wire rod become homogenized. In this case, the difference between the interlayer spacing in the surface layer and the interlayer spacing in the central region does not increase sufficiently. Furthermore, if the cooling time immediately after rolling is too long, the deviation in the interlayer spacing in the surface layer increases.

[0326] If water cooling begins within 0.5 seconds of the final finishing rolling, the austenite grains in the surface layer are easily maintained in a fine state. As a result, the difference between the interlaminar spacing in the surface layer and the central region increases significantly, with FWHMc / FWHMs reaching 1.10 or higher. Furthermore, because the surface layer is water-cooled immediately after the final finishing rolling, the austenite grains in the surface layer are refined, causing the pearlite phase transformation to occur at a high speed. Therefore, overall deviations in the interlaminar spacing in the surface layer can be suppressed. As a result, LmaxS / LaveS reaches 1.70 or lower. It should be noted that the coiling temperature of the wire is 700°C or higher.

[0327] It should be noted that the finished wire rod is coiled. The coiled wire rod is then subjected to forced-air cooling for further cooling. In this embodiment, no rapid heating or other heating processes are performed while the coiled wire rod is at room temperature.

[0328] The wire of this embodiment can be manufactured through the above manufacturing process.

[0329] [Methods for manufacturing steel wire]

[0330] The method for manufacturing hardened steel wire using the wire material of this embodiment as raw material is a well-known manufacturing method. The steel wire is, for example, steel cord. The method for manufacturing steel wire using the wire material of this embodiment is as follows: The oxide scale of the wire material is removed, and a lubrication treatment is performed. The lubricated wire material is then subjected to dry drawing to manufacture steel wire. The dry-drawn steel wire is subjected to a well-known sorbitizing treatment and a well-known plating treatment. A wet drawing process is then performed. Through the above manufacturing steps, steel wire is manufactured.

[0331] In the wire of this embodiment, the deviation of the interlayer spacing is suppressed to a certain extent, while the ratio of the deviation between the surface layer and the central region is increased to a certain extent. As a result, sufficient wire drawing workability is obtained in the steel wire after dry drawing.

[0332] Example

[0333] The effects of the cable according to this embodiment will be explained more specifically through examples. The conditions in the following examples are examples used to confirm the feasibility and effects of the cable according to this embodiment. Therefore, the cable according to this embodiment is not limited to this one example.

[0334] The following methods were used to manufacture wires having the chemical compositions shown in Tables 1-1 and 1-2.

[0335] [Raw Material Preparation Process]

[0336] Raw materials (steel blocks) with the chemical compositions shown in Tables 1-1 and 1-2 were manufactured.

[0337]

[0338]

[0339] [Blank rolling process]

[0340] The manufactured steel blocks were subjected to a roughing rolling process to produce steel billets. Specifically, the steel blocks were heated to 1100°C using a heating furnace. The heated steel blocks were then hot-rolled (roughed) using a roughing mill and a continuous rolling mill to produce steel billets. The cooling rate CR (°C / second) after hot rolling at 700~670°C is shown in Table 2.

[0341]

[0342] [Finishing rolling process]

[0343] The manufactured steel billets underwent a finishing rolling process. Specifically, a heating furnace was used to heat the steel billets of each test number to 950~1150℃.

[0344] Wire rods were manufactured by finishing the heated steel billets using a continuous rolling mill. The finishing rolling temperatures (°C) are shown in Table 2.

[0345] For tests 1-41, the time t from the end of final finishing rolling to the start of water cooling was less than 0.5 seconds (indicated by "T(True)" in the "Time t≤0.5 seconds" column of Table 2). On the other hand, for tests 42-45, the time t from the end of final finishing rolling to the start of water cooling exceeded 0.5 seconds (indicated by "F(False)" in the "Time t≤0.5 seconds" column of Table 2). Water cooling was then performed until the wire temperature reached 800°C. It should be noted that the coiling temperature was above 700°C. After coiling, the wire was cooled to room temperature by forced air cooling without reheating. Wire with a diameter of 5.5 mm was manufactured through the above manufacturing process.

[0346] For all manufactured wires, the oxide scale was removed and lubrication treatment (phosphate treatment) was performed under the same conditions for each test number. The lubricated wires were then subjected to dry drawing to produce steel wires with a diameter of 1.5 mm. During the drawing process, a die with a 10° (full angle) was used, and the wire speed was set to 10 m / min.

[0347] [Regarding the evaluation test]

[0348] The following evaluation tests (Test 1 and 2) and steel wire tests (Test 3) were conducted on the manufactured wires and steel wires for each test number.

[0349] (Experiment 1) Pearlite Area Ratio Determination Experiment

[0350] (Experiment 2) Determination of LaveS, LmaxS, FWHMc and FWHMs

[0351] (Experiment 3) Torsion Test

[0352] The following is a description of each experiment.

[0353] [(Experiment 1) Pearlite Area Ratio Measurement Experiment]

[0354] The pearlite area ratio (%) of the wires for each test number was determined using the method described in the [Method for Determining Pearlite Area Ratio] above. The results are shown in Table 2. In all test numbers, the pearlite area ratio was 95% or higher. It should be noted that the balance other than pearlite was selected from one or more of ferrite, primary cementite, bainite, and martensite.

[0355] [(Experiment 2) Determination of LaveS, LmaxS, FWHMc and FWHMs]

[0356] For the wires of each test number, the methods described in the above-mentioned [Measurement Methods for LaveS, LmaxS, FWHMc and FWHMs] were implemented [regarding the true interlayer spacing λ]. t Following steps 1 to 3 of the method for determining the distribution of [ ], LaveS (nm), LmaxS (nm), FWHMc, and FWHMs were obtained. The results are shown in Table 2.

[0357] [(Experiment 3) Torsion Test]

[0358] For the steel wires of each test number, torsion tests were performed as described below.

[0359] First, the tensile strength of the steel wire for each test number was determined using the following method. The steel wire was cut into 340mm lengths and straightened. The straight wire was clamped at the top and bottom 70mm, with a chuck spacing of 200mm. A tensile test was conducted at room temperature and in atmospheric conditions, and the tensile strength TS (MPa) was determined.

[0360] Furthermore, test pieces for torsion testing were taken from the steel wires of each test number. In the test pieces, the chuck spacing was set to wire diameter d × 100 mm. Then, the end 50 mm of the test piece was clamped. A load of 0.1 × TS was applied to the test pieces, and a torsion test was performed. The torsion speed was set to 20 rpm. For each test number, three test pieces were subjected to torsion tests. The number of torsions until final fracture was calculated, and the arithmetic mean of the number of torsions obtained from the three pieces was calculated. Based on the obtained arithmetic mean of the number of torsions TC and the tensile strength TS, the following evaluation values ​​were obtained.

[0361] Evaluation value = TC × TS

[0362] If the evaluation value is 70,000 or higher, it is judged as having excellent wire drawing processability (indicated by "E (Excellent)" in the "TC×TS≥70000" column of Table 2). On the other hand, if the evaluation value is less than 70,000, it is judged as having insufficient wire drawing processability (indicated by "B (Bad)" in the "TC×TS≥70000" column of Table 2).

[0363] [Experimental Results]

[0364] The test results are shown in Table 2. Referring to Tables 1-1, 1-2, and 2, the wires tested from 1 to 37 met characteristics 1 to 3. As a result, the evaluation value was above 70,000, indicating excellent wire drawing properties.

[0365] On the other hand, in tests 38-41, the cooling rate under condition 1 was too fast. Therefore, FWHMc / FWHMs was less than 1.10. As a result, the evaluation value was less than 70000, and sufficient wire drawing processability was not achieved.

[0366] In tests 42-45, the time t from the end of the final finishing rolling to the start of water cooling exceeded 0.5 seconds. Therefore, LmaxS / LaveS exceeded 1.70. Furthermore, FWHMc / FWHMs was less than 1.10. As a result, the evaluation value was less than 70000, indicating insufficient wire drawing workability.

[0367] The embodiments of this disclosure have been described above. However, the above embodiments are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and can be implemented by making appropriate modifications without departing from its spirit.

Claims

1. A wire having a chemical composition containing, in mass %: Si: 0.10 to 1.50%, Mn: 0.10 to 1.00%, P: 0.020% or less, S: 0.020% or less, Al: 0.080% or less, O: 0.0050% or less, Co: 0 to 0.50%, Cu: 0 to 0.50%, Ni: 0 to 0.50%, Mo: 0 to 0.20%, Ti: 0 to 0.10%, Nb: 0 to 0.10%, Sn: 0 to 0.10%, As: 0 to 0.050%, Sb: 0 to 0.050%, Ca: 0 to 0.0050%, Mg: 0 to 0.0050%, Zr: 0 to 0.010%, and rare earth element: 0 to 0.0050%, the balance consisting of Fe and impurities, wherein in a circular cross section perpendicular to the axial direction of the wire, the average value of the real interlayer spacing at a depth position of 0.5 mm from the surface of the wire is set as LaveS (nm), the maximum value of the real interlayer spacing is set as LmaxS (nm), and LmaxS / LaveS is 1.70 or less, and wherein in the circular cross section, the full width at half maximum of the real interlayer spacing at the depth position of 0.5 mm from the surface of the wire is set as FWHMs (nm), the full width at half maximum of the real interlayer spacing at the center position of the wire is set as FWHMc (nm), and FWHMc / FWHMs is 1.10 to 2.

00. C:0.70~1.20%、 2. The wire according to claim 1, wherein the chemical composition contains one or more selected from the group consisting of: Co: 0.01 to 0.50%, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.50%, Mo: 0.01 to 0.20%, Ti: 0.01 to 0.10%, Nb: 0.01 to 0.10%, Sn: 0.01 to 0.10%, As: 0.001 to 0.050%, Sb: 0.001 to 0.050%, and the balance consisting of Fe and impurities, in mass %.

3. The wire according to claim 1 or 2, wherein the chemical composition contains one or more selected from the group consisting of: Ca: 0.0001 to 0.0050%, Mg: 0.0001 to 0.0050%, Zr: 0.001 to 0.010%, and rare earth element: 0.0001 to 0.0050%, in mass %. ​ ​ ​ N:0.0010~0.0100%、 ​ Cr:0~0.50%、 ​ ​ ​ ​ B:0~0.005%、 W:0~0.20%、 ​ ​ ​ ​ ​ V:0~0.10%、 ​ ​ ​ ​ ​ ​ ​ ​ ​ Cr:0.01~0.50%、 ​ ​ ​ ​ B:0.001~0.005%、 W:0.01~0.20%、 ​ ​ ​ ​ ​ V:0.01~0.10%。 ​ ​ ​ ​ ​ ​

Citation Information

Patent Citations

  • High carbon steel wire rod having excellent dry wire drawability and method for producing the same

    JP2012126955A

  • High carbon steel wire having excellent drawability

    WO2016021556A1

  • Wire rod

    WO2018117157A1